The fringes of the official and the unofficial in teachers’ electronic correspondence - Piechnik, Anna (Papers in Linguistics, 2023)
The article presents the area on the fringes of the official and unofficial styles in electronic correspondence sent by teachers to parents. The research material consists of e-mails sent by 112 teachers to multiple addressees – groups of parents of students from over a dozen schools at various levels of education. For the purposes of the study, a survey on teachers’ electronic communication was also conducted in 2022 among 370 educators. In the questionnaires, teachers declared their attention to adapting the linguistic shape of an electronic letter to the patterns known from traditional official paper correspondence (including the use of initial and final formal polite formulas or signing their messages with name and surname). E-mailing was considered the most common form of contact with parents, a form which required special care for the linguistic side of the text. Authentic texts of e-mails show that the actual outcomes diverge considerably from teachers’ declarations. The politeness frame of the scrutinized e-mails rarely contains official formulas, and the traditional distance typical of contacts between parties remaining in a formal relationship is also broken with the use of colloquial vocabulary and emoticons. The teachers’ statements indicate that electronic letters addressed to parents with whom the contact is difficult remain more official, while they are more willing to send messages without official markers to groups of parents who are friendly. This may point to a new function of officiality which denotes deprecation, and a different evaluation of this category, diverging from the traditional one.